Proceedings of the 2015 2nd International Conference on Machinery, Materials Engineering, Chemical Engineering and Biotechnolog 2016
DOI: 10.2991/mmeceb-15.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation precipitation of manganese from electrolytic manganese residue treated by CO2 with alkaline additives

Abstract: Abstract. This work reports the results of carbonate precipitation of soluble manganese by CO 2 with alkaline additives with the aim of eliminating the harm caused by electrolytic manganese residue (EMR). Results showed that CaO exhibited a better performance for the precipitation of manganese which was converted to rhodochrosite (MnCO 3 ) by infrared spectra and XRD analyses and that the precipitation rate of manganese reached 99.99% at 800 mL/min CO 2 flow rate and 5% CaO for 20 min reaction time. The leache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some scholars have conducted studies on pollutant management in EMR. Chen and co-workers 18,19 have shown that the content of Mn 2+ and NH 4 + -N is lower than that of fresh EMR and that there is a disappearance of FeS 2 , MnSO 4 • H 2 O, and (NH 4 ) 2 SO 4 in the stockpiled EMR. Zhou et al 20 have shown that Mn wrapped by colloids and Mn in the stable chemical state were not easily dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have conducted studies on pollutant management in EMR. Chen and co-workers 18,19 have shown that the content of Mn 2+ and NH 4 + -N is lower than that of fresh EMR and that there is a disappearance of FeS 2 , MnSO 4 • H 2 O, and (NH 4 ) 2 SO 4 in the stockpiled EMR. Zhou et al 20 have shown that Mn wrapped by colloids and Mn in the stable chemical state were not easily dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…China has been the top contributor to the production of electrolytic metal manganese, accounting for over 98.5% of the total world capacity in 2014. , The recycling of EMS has become a major problem for the industry. Many scientists and engineers have studied recycling of EMS and have made progress in many approaches, including synthesis of zeolite, geopolymers, road beds, soil fertilizer, autoclaved bricks, ground granulated blast-furnace slag cement, cementing material, chemical raw materials, and metal recovery. , These methods are very difficult to be applied industrially because of low efficiency, high cost of production, and low value of the resultant products. The recycling of EMS is still limited to laboratory scales while the increasing quantity of EMS is being stacked near factories, causing potential pollution from the heavy metals of EMS as rain soaks EMS over a long period of time.…”
Section: Introductionmentioning
confidence: 99%